ESCAPE FROM FREEDOM IN WILLIAM SHAKESPEARE'S DRAMA ANTONY AND CLEOPATRA: AN EXISTENTIALIST CRITICISM - INDRAWATI , INDRAWATI (2010)
The object of the study is the drama script of Antony and Cleopatra play written by William Shakespeare. The study is to reveal escape from freedom is reflected in Antony and Cleopatra written by William Shakespeare. The objective of the study is to analyze the structural element in the play and to analyze the escape from freedom of the play based on an existentialist criticism. The research employs the descriptive qualitative research as a type of the research. The data sources are divided into two, namely primary data sources and secondary data sources. The primary data sources are the dialogues, statements, and actions of the Antony and Cleopatra drama script and the secondary data sources is biography of character. The method of collecting data is note taking. The technique of analyzing data is descriptive. The result of the study is as follows. Firstly, based on the structural analysis, the play suggests that freedom is a burden that not everyone can hold and the structural elements are related each other and form a unity. Secondly, based on the existentialist perspective, Shakespeare represents an existential situation in which individuals escape from the burden of freedom in Antony and Cleopatra play.